THE EXPERIMENTAL STUDY IN THE CLASSROOM FOR THE ESTABLISHMENT OF THE ACCOUNTING STUDENTS’ SOFT SKILL THROUGH EFFECTIVE TEAM BUILDING - Surjawati Surjawati; Dian Indriana Tri Lestari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
An accounting education graduate is required to master hard skills and soft skills. In terms of mastering soft skills in the accounting profession, it means to work together as a team. This soft skill provision is obtained through effective learning methods by forming a team that is given the assignment to solve a problem and accounts for it through presentations. The purpose of this study is to provide guidelines for lecturers to build effective teams for students. This study uses a descriptive experimental approach conducted by researchers in 5th semester students with Business Mixing Accounting courses. Team formation refers to McGrath’s Model framework. This model includes the input, process, and output stages. The input phase emphasizes the quality of the teams from various inputs. The larger the team, the more personality types, and time variations will be accommodated and the more conflicts that will be faced. The stage of the process includes how members deal with conflict and make conflict a success. The output stage includes criteria for measuring group performance results and other measures such as member performance satisfaction, group cohesiveness at the end of the task, and changes in member behavior to be better